2018
DOI: 10.1029/2018sw001822
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Lasting Geomagnetically Induced Currents and Harmonic Distortion Observed in New Zealand During the 7–8 September 2017 Disturbed Period

Abstract: Several periods of geomagnetically induced currents (GICs) were detected in the Halfway Bush substation in Dunedin, South Island, New Zealand, as a result of intense geomagnetic storm activity during 6 to 9 September 2017. Unprecedented data coverage from a unique combination of instrumentation is analyzed, that is, measurements of GIC on the single‐phase bank transformer T4 located within the substation, nearby magnetic field perturbation measurements, very low frequency (VLF) wideband measurements detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 33 publications
5
85
0
Order By: Relevance
“…This result is also consistent with a similar case study performed by for the 6-7 April 2000 geomagnetic storm, although their GIC readings in the same pipeline were smaller than in this case. Further evidence of a substorm during this time was reported by Clilverd et al (2018) based on the Wp index (Nosé et al, 2012). Similar to this study and around the same UT time, Clilverd et al (2018) showed enhanced GICs of almost 35 A at the Halfway Bush substation in Dunedin, South Island, New Zealand.…”
Section: Observationssupporting
confidence: 87%
See 1 more Smart Citation
“…This result is also consistent with a similar case study performed by for the 6-7 April 2000 geomagnetic storm, although their GIC readings in the same pipeline were smaller than in this case. Further evidence of a substorm during this time was reported by Clilverd et al (2018) based on the Wp index (Nosé et al, 2012). Similar to this study and around the same UT time, Clilverd et al (2018) showed enhanced GICs of almost 35 A at the Halfway Bush substation in Dunedin, South Island, New Zealand.…”
Section: Observationssupporting
confidence: 87%
“…As previous studies have shown (Anderson & Fuselier, ), this reiterates that the EE is also important to driving large GICs. It is particularly worth noting that this interval also appeared to be part of a larger global response (Clilverd et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Instead, SCs are known to often be followed by prolonged magnetospheric activity that can result in damaging GICs Pulkkinen et al (), Clilverd et al (). We have shown that, for the United Kingdom, the percentiles of R are elevated above background levels for 3 days following an SC.…”
Section: Discussionmentioning
confidence: 99%
“…This explosion produced a Coronal mass ejections (CME) and triggered a geomagnetic storm on 7 September. Many studies have investigated the ionospheric responses to the geomagnetic storm (e.g., Aa et al, 2018;Clilverd et al, 2018;Jin et al, 2018;Lei et al, 2018;Li et al, 2018;Yamauchi et al, 2018). Figure 2a shows the X-ray flux variation at the interval of 10-15 UT on 6 September.…”
Section: Datamentioning
confidence: 99%